Reduced field of view single‐shot spiral perfusion imaging. Issue 1 (20th March 2017) - Yang, Yang; Zhao, Li; Chen, Xiao; Shaw, Peter W.; Gonzalez, Jorge A.; Epstein, Frederick H.; Meyer, Craig H.; Kramer, Christopher M.; Salerno, Michael
Abstract : Purpose: To develop a single‐shot spiral perfusion pulse sequence with outer‐volume suppression (OVS) to achieve whole‐heart coverage with a short temporal footprint of 10 ms per slice location. Methods: A highly accelerated single‐shot variable density spiral pulse sequence with an integrated OVS module for reduced field of view (rFOV) perfusion imaging with 2 mm spatial resolution was developed and evaluated in simulations, phantom experiments and in clinical patients with (n = 8) or without (n = 8) OVS. Images were reconstructed by block low‐rank sparsity with motion guidance (BLOSM) and graded by two cardiologists on a 5‐point scale (1, excellent; 5, poor). Results: Simulation and phantom results showed that OVS effectively suppressed the signal outside the desired field of view (FOV). Clinical patient data demonstrated high quality perfusion images with rFOV. The average image quality scores of full FOV cases and rFOV cases were 3.1 ± 0.64 and 2.3 ± 0.46, respectively, ( P = 0.02) from cardiologist 1 and 2.5 ± 0.54 and 1.8 ± 0.47, respectively, ( P = 0.04) from cardiologist 2, showing superior image quality for the rFOV images compared with the full FOV images. Conclusion: A single‐shot spiral perfusion sequence that uses OVS and BLOSM performs perfusion imaging with a very short temporal footprint per image supporting whole‐heart coverage with good image quality. Magn Reson Med 79:208–216, 2018. © 2017 International Society for Magnetic Resonance in Medicine.